The effect of cognitive behavioural therapy for insomnia on sedative-hypnotic use: A narrative review. (April 2021) - Sweetman, Alexander; Putland, Stacey; Lack, Leon; McEvoy, R.Doug; Adams, Robert; Grunstein, Ron; Stocks, Nigel; Kaambwa, Billingsley; Van Ryswyk, Emer; Gordon, Christopher; Vakulin, Andrew; Lovato, Nicole
Summary: Although cognitive behavioural therapy for insomnia (CBTi) is the recommended 'first-line' treatment for insomnia, most patients are initially treated with sedative-hypnotic medications. Given the risk of impaired cognitive and psychomotor performance, serious adverse events, and long-term dependence associated with sedative-hypnotics, guidelines recommend that prescriptions should be limited to short-term use and that patients are provided with support for withdrawal where possible. CBTi is an effective insomnia treatment in the presence of sedative-hypnotic use. Furthermore, guidelines recommended that CBTi techniques are utilised to facilitate withdrawal from sedative-hypnotics. However, there is very little research evaluating the effect of CBTi on reduced medication use. The current narrative review integrates 95 studies including over 10, 000 participants, investigating the effect of CBTi on reduced sedative-hypnotic use in different populations (e.g., hypnotic-dependent patients, older adults, military personnel), settings (e.g., primary care settings, psychiatric inpatients), CBTi modalities (e.g., self-administered reading/audio materials, digital, and therapist-administered), and in combination with gradual dose reduction programs. Based on this research, we discuss the theoretical mechanistic effects of CBTi in facilitating reduced sedative-hypnotic use, provide clear recommendations for future research, and offer pragmatic clinical suggestions to increase access to CBTi to reduce dependence on sedative-hypnotics as the 'default' treatment for insomnia.